MEMICU VISUALISASI DAN KREATIVITAS DALAM PEMBELAJARAN MATEMATIKA MEMBENTUK KARAKTER POSITIF SISWA - Edy Surya (JURNAL TEMATIK, 2014)
Achievement various Indonesian student in International Olympic event apparently did not make the quality of Indonesian students increases. On the contrary , about 76.6 percent of junior high school students turned out to be judged " blind " math . Sometimes teachers forget and do not realize the students' mathematics learning experience that is small compared to the learning experience of teachers who has a dozen years . Teachers want what is given in the learning of the student should be able to master . Whereas the absorption ability of the students and the other is not the same . Difficulties experienced by students and low yields can be attributed math teacher delivery methods that are not in accordance with the teaching materials , experiences and abilities of students . Teachers can guide students to imagine (visualize) mathematical problem solving, and encourage the creativity of students in the mastery of concepts or mathematical ability, so as to improve learning outcomes and positive character of students.